PCOS in adolescence: effect of metformin on menstrual irregularities - Sontakke, Bhavana Vaikunth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: PCOS is an endocrine disorder affecting women across lifespan, initially a disease of the females in the child bearing age group, nowadays maximum adolescent females also present with PCOS. Adolescence PCOS is a heterogenous endocrine disorder diagnosed in 5% to 10% of adolescent girls and is one of the major causes of adolescent hyperandrogenism and menstrual irregularity. Thus, this study was carried out to study the effect of Metformin on adolescent patients with PCOS on Weight reduction and Regularization of Menstrual cycle. Secondary objective is to study the occurrences of various manifestations in patients with PCOS. Methods: Patients aged 10-20 years diagnosed PCOS attending the outpatient department of OBGY over a period of two years were included in the study. Out of 100 patients, 20 patients were excluded because of other causes of anovulation viz thyroid abnormalities, prolactin level abnormalities and patients who did not turn up for follow up. Study was done on 80 patients of PCOS. Patients were divided into two groups A and B. Group A (n=40) received 500 mgs Metformin and Group B (n=40) received placebo. Results were analysed using statistical package of social sciences (SPSS) 21.0. Statistical significance was set at p ≤0.05. Results: In the present study Irregular cycle was the commonest occurring menstrual irregularity. Menstrual Cycle was regularised in 95% of the study group while only 35% of the control group. 85% patients in the present test group had lost weight at the end of 6 months while only 55% in the control group had lost weight in 6 months. Thus A 6-month course of metformin improves menstrual cyclicity in women with the PCOS. Conclusions: In patients with PCOS, the addition of insulin sensitizers viz metformin along with diet and lifestyle modifications has resulted in significant weight loss and improvement in cyclicity of menstrual cycle. Thus, Insulin-sensitizing agents provide a rational approach to the treatment of the metabolic and endocrine abnormalities in PCOS women